1963
DOI: 10.1111/j.1365-2621.1963.tb01678.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heating Time and Temperature on the Shear of Beef Semitendinosus Muscle a

Abstract: The effect of time and temperature on the shear patterns of small cylinders from individual choice-grade beef semitendinosus muscles, heated for several hours at 1°C intervals between 50 and 90°C is described.Beef semitendinosus muscle undergoes a marked decrease in shear, approximately one-half eompleted in 11 min at 58°C. This change in shear is a time-temperature rate process having a very high temperature dependence.Minimum shear values were obtained in the range of 60-64'C after heating for 3040 min. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

1974
1974
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 7 publications
5
41
1
Order By: Relevance
“…Laakkonen et al (1970) concluded that the major decrease in Warner-Bratzler (WB) peak shear force values obtained when beef muscles were heated at a slow rate occurred at SO-60°C. This confirmed earlier work (Machlik and Draudt, 1963;Tuomy et al, 1963;Draudt et al, 1964) which showed that a large decrease in shear force values occurred between 50 and 65°C. Other workers (Bramblett et al, 1959;Bramblett and Vail, 1964;Bayne et al, 1969) reported that cooking meat by holding in an oven at relatively low oven temperatures (<120"(Z) for up to 30 hr produced meat more tender than that cooked at the usual higher temperatures.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Laakkonen et al (1970) concluded that the major decrease in Warner-Bratzler (WB) peak shear force values obtained when beef muscles were heated at a slow rate occurred at SO-60°C. This confirmed earlier work (Machlik and Draudt, 1963;Tuomy et al, 1963;Draudt et al, 1964) which showed that a large decrease in shear force values occurred between 50 and 65°C. Other workers (Bramblett et al, 1959;Bramblett and Vail, 1964;Bayne et al, 1969) reported that cooking meat by holding in an oven at relatively low oven temperatures (<120"(Z) for up to 30 hr produced meat more tender than that cooked at the usual higher temperatures.…”
Section: Introductionsupporting
confidence: 93%
“…According to one suggestion (Davey and Niederer, 1977), during heating to 65°C meat is tenderized by specific proteolytic attack on the myofibrillar structure (i.e., accelerated aging) and above 70°C there is a destruction or weakening of the collagenous connective tissue. This interpretation does not agree with other published work (Machlik and Draudt, 1963;Tuomy et al, 1963;Draudt et al, 1964;Bramblett et al, 1959;Bramblett and Vail, 1964;Bayne et al, 1969;Laakkonen et al, 1970;Penlield and Meyer, 1975) which suggests that collagen is weakened at temperatures well below 70°C. If prolonged heating in the 5@65"C range acted only via proteolysis of the myofibrillar structure, then the usefulness of such treatments would be limited, since it has been demonstrated (Ratcliff et al, 1977), using a pressure-heat method, that decreasing myofibrillar strength alone does not make all meat tender.…”
Section: Interpretation Of Resultscontrasting
confidence: 70%
“…It is known that collagen heated to about 60°C shortens and is converted to a more soluble form. 4 The percentage of collagen solubilised by heating increases gradually as the temperature is increased from 60 to 90°C.5 Gelatin formation is swift with pressure cooking.6 As it includes an autoclave step, the extraction method of Milgrom and Witebsky3 provides conditions favourable for the conversion of collagen to gelatin. Gelatin and other irrelevant proteins in these preparations are undesirable, as they may interfere at various stages with EIA.…”
Section: Introductionmentioning
confidence: 99%
“…Shear force values were found to decrease rapidly first between 58 and 60°C and then again at 71-75°C becoming more pronounced with increasing temperature (Machlik and Draudt 1963). They (Machlik and Draudt 1963) concluded that the marked decline in shear force values a t 58°C was due to collagen shrinkage and between 71-75°C was due to the degradation of collagen fibers. Rigby (1964) reported that stretching or contracting the myofibrillar structure could stress the connective tissue network, thus decreasing the collagen shrinkage temperature.…”
Section: Connective Tissuesmentioning
confidence: 92%